Extraction of the essential oil of Aquilaria Malaccensis (gaharu) using hydro-distillation and solvent extraction methods - Ashwin Charles, Benedict (2009)
Agarwood oil is regarded as one of the most expensive natural products in the world due to the fragrance inducing compounds it contains. However, current studies on the chemical composition of agarwood essential oil are woefully lacking and this poses a threat to the agarwood industry. This research aims to identify the best extraction method for isolating gaharu essential oil and to create a list of compounds contained in a sample of grade C agarwood. In the present work, the composition of agarwood essential oil obtained through hydro-distillation and solvent extraction with acetone, dichloromethane and hexane as the solvents were analyzed for marker compound identification using gas chromatography-mass spectrometry (GC-MS). Studying another parameter of this experiment, the sample hydro-distillated in the lab was compared with industrial grade hydro-distillation to determine the difference in quality between industrial and lab scale hydro-distillation. Of the three solvents used, acetone eluted the highest number of compounds. The lab scale hydro-distillated sample eluted 34 compounds at a quality of 50% and above whereas the solvent extraction sample eluted 25 compounds. There was no significant difference found between lab scale and industrial scale hydro-distillation.